Implementation of Project-Based Simple Science Media in Science Learning: Strengthening Mutual Cooperation, Critical, and Creative Reasoning of Elementary School Students - Farah Nailis Saniyyah; Nasokah Nasokah; Ashief El-Qorny (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Social studies learning in the Independent Curriculum requires a contextual, participatory, and oriented learning experience that strengthens the Pancasila Student Profile. However, learning practices in elementary schools still tend to be dominated by conventional approaches, so that students' active involvement in understanding science concepts and developing character is not optimal. This study aims to describe the implementation of project-based science media through Volta Drive Connect, analyze student responses, and strengthen the three-dimensional Pancasila Student Profile in science learning. This study used a descriptive qualitative approach with 18 grade IV students of Kakuka National Elementary School. Data was collected through observation, interviews, and documentation. Data analysis uses the interactive model of Miles, Huberman, and Saldana through the stages of data reduction, data presentation, and conclusion drawing and verification. The results showed that implementing Volta Drive Connect encouraged active student involvement throughout the learning process. Indicators of mutual cooperation are evident in the sharing of roles during collaborative assembly, discussion, retrying, and problem-solving activities. The indicators of mutual cooperation were evident in group cooperation (88.9%), role sharing (77.8%), and mutual help (83.3%). Critical reasoning indicators were seen through the ability to ask questions 66.7%, analyze problems 72.2%, and draw conclusions 61.1%. Meanwhile, creative indicators emerged in the ability to generate ideas (72.2%), try alternative solutions (83.3%), and modify the results of work (55.6%). The novelty of this research lies in the use of simple science media that connect the concept of energy to daily life and also show the strengthening of students' character that develops during the learning process. Thus, project-based simple science media can be an alternative to IPAS learning that is contextual and meaningful, and that supports the strengthening of the Pancasila Student Profile.